Odpowiedzi

Najlepsza Odpowiedź!
2010-04-08T19:14:17+02:00
A) P = d/M * RT
d/M * RT = P / d/M
RT = P*(M/d)
RTd = PM / : P
RTd/P = M

b) f = (9/5)c + 32
(9/5)c + 32 = f / *5
9c + 32*5 = 5f
9c + 160 = 5f
c + 5f/9 - 160/9
c = (5f-160)/9

c) S = vt + at²/2
at²/2 + vt = S /*2
at² = 2s - 2(vt) / :t²
a = 2S-2(vt)/t²
a = 2(S-vt)/t²

d) F = G * Mm/r²
G * Mm/r² = F / *r²
GMm = Fr² /:GM
m = Fr²/GM
2010-04-08T19:18:00+02:00
A)p=d/m *RT /*M
PM=dRT /:P
M=dRT:P

b)f=9/5c+32 /*5
5f=9c +32 /-32
5f-32=9c /:9
c= 5f - 32:9

c)s=vt+at(kwadrat):2 /*2
2s=vt+at(kwadrat) /-vt
2s-vt=at(kwadrat) /-t(kwadrat)
2s-vt - t(kwadrat)=a

d)F=G*Mm/r(kwadrat) /*r(kwadrat)
Fr(kwadrat)=G*M(kwadrat) /:G
(Fr(kwadrat):G) =M(kwadrat) /:m
Fr(kwadrat):Gm = m